2017
DOI: 10.3892/ol.2017.7384
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression of the high‑mannose M6N2 and NeuAc3H3N3M3N2F tri‑antennary N‑glycans in cholangiocarcinoma

Abstract: Changes in protein glycosylation have been reported in various types of cancer, including cholangiocarcinoma (CCA). Nanospray ionization-linear ion trap mass spectrometry (NSI-MSn) was used in the present study to determine the comparative structural glycomics of the N-linked glycans in the serum of patients with CCA compared with healthy controls. A total of 5 high-mannose and 4 complex N-linked glycans were detected. Mannose7-N-acetyl-glucosamine2 was the most abundant structure among the high-mannose types … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 28 publications
(33 reference statements)
1
14
0
Order By: Relevance
“…In our study, high-mannose (M9) and core-fucosylated (FA2G2S1) plasma glycan species were significantly decreased in the PTSD group, compared to the low-stress healthy control, and this result corresponds to lower glycan species found in inflammation [34]. As alternations of high-mannose glycans have been associated with occurrence and progression of different types of cancers [38][39][40], neuropsychiatric disorders [41], inflammation [34] and brain aging [42], whereas PTSD is associated with inflammation [17] and cardiometabolic disorders [4,5], the lower FA2G2S1 glycan result suggests that veterans with PTSD should be closely monitored for these disorders.…”
Section: N-glycans In Plasmasupporting
confidence: 47%
“…In our study, high-mannose (M9) and core-fucosylated (FA2G2S1) plasma glycan species were significantly decreased in the PTSD group, compared to the low-stress healthy control, and this result corresponds to lower glycan species found in inflammation [34]. As alternations of high-mannose glycans have been associated with occurrence and progression of different types of cancers [38][39][40], neuropsychiatric disorders [41], inflammation [34] and brain aging [42], whereas PTSD is associated with inflammation [17] and cardiometabolic disorders [4,5], the lower FA2G2S1 glycan result suggests that veterans with PTSD should be closely monitored for these disorders.…”
Section: N-glycans In Plasmasupporting
confidence: 47%
“…Earlier studies affirm that while glycans regulate the catalytic activity of certain proteins, others may not be affected by glycosylation changes (29,43). The ability to trace glycans to their parent proteins is necessary to interpret how alterations in glycan expression patterns lead to enhancement of metastatic phenotypes but is lacking in earlier studies (44). Our approach evaluated extended high-mannose glycans together with their parent glycoproteins.…”
Section: Discussionmentioning
confidence: 99%
“… 12 Notably, a lectin microarray-based sero-biomarker has been reported for the detection of O -linked glycosylation in patients with cholangiocarcinoma; 13 cholangiocarcinoma cell lines exhibit differential expression of O -glycans, based on the histological type of cholangiocarcinoma. 14 Our prior research revealed elevated expression of N -linked glycoprotein glycans in serum from patients with cholangiocarcinoma, compared with healthy controls; 15 elevated glycosphingolipid levels have also been associated with shorter survival in patients with cholangiocarcinoma. 16 …”
Section: Introductionmentioning
confidence: 98%